An analysis of international relations from a theory of argumentation: the case of the invasion to iraq (2008)
The basic aspects of the theory of argumentation, the relations of argumentation with the concept of logical inference and a description of argumentation in the analysis of compared international politics are presented in this article. Argumentation will be here understood as part of a deliberative process of pro or against reasoning around certain opinion that might be defended by means of a confrontation of ideas. Therefore, the one who argues proposes, refuses, beats or justifies any understanding of the world. With this in view, a brief description of deductive argumentative systems is undertaken. Some degree of formality, arising from the logics to structure the general argumentative basis, is introduced. Then, an exemplification based on a highly recognized case in international relations is presented: the conditions of public debate that gave birth to the invasion and war in Iraq.